(untitled) (Bangladesh Medical Journal Khulna, 2019)
Background: nfectious diarrhoea is a major public health problem in developing countries like Bangladesh. Bacteria and parasites are important etiological agents for diarrhoea in infants and children. Objectives: To isolate and identify the causative organisms of diarrhoea from diarrhoeal stools in under 5 children. Methodology: This was an observational cross sectional study carried out at Microbiology Department of Sir Salimullah Medical College, Dhaka. A total of 217 diarrhoeal patients upto 5 years age, attending Pediatric unit of Sir Salimullah Medical College and Mitford Hospital, Dhaka and Dhaka Shishu Hospital, Dhaka during the period of July 2015 to June 2016, were enrolled in the study. For isolation of enteric bacteria, diarrhoeal stools were inoculated on Mackonkey agar media and for Campylobacter spp. diarrhoeal stools were inoculated on selective Modified Campy-BAP media and nonselective Blood agar media with membrane filter. Positive culture was confirmed by Gram stain morphology and standard biochemical tests. Oocysts of Cryptosporidium were identified by Modified Ziehl Neelsen staining and other parasites were identified by wet mount preparation. Results: Out of 217 diarrhoeal stools bacteria were isolated from 97 (44.7%) patients. Among 97 cases, Escherichia coli were detected in 51(52.58%) patients; Campylobacter spp. were detected in 23(23.71%) patients; Shigella spp. were detected in 15(15.46%) patients and Salmonella spp. were detected in 8(8.25%) patients. Microscopic finding of diarrhoeal stools were detected by pus cells with or without RBCs in 90(70.31%) samples. Cysts of Giardia intestinalis were found in 9(4.14%) samples, cysts of Entamoeba histolytica in 2(0.9%) samples, eggs of Trituris trichiura in 2(0.9%) samples and oocysts of Cryptosporidium were found in.5(2.30%) samples. Conclusion: Escherichia coli was the most common bacteria and Giardia intestinalis was predominant parasite causing diarrhoea in under 5 children. Bang Med J (Khulna) 2018; 51 : 25-28